A fundamental relationship between TCR diversity, repertoire size and systemic clonal expansion: insights from 30,000 TCRβ repertoires - Zahid, H. Jabran; May, Damon; Robins, Harlan; Greissl, Julia (Frontiers in Immunology, 2026)
IntroductionT cell receptor (TCR) diversity is essential for immune defense, yet the mechanisms underlying its decline with age and its variation among individuals remain poorly understood. These patterns are typically attributed to passive processes such as thymic atrophy and cumulative immune exposures. However, this view does not account for the systematic and highly structured variation in TCR diversity observed across large populations.MethodsWe analyze TCRβ repertoires from approximately 30,000 adults using high throughput sequencing. We quantify repertoire size and the contribution of the most expanded clones and evaluate their ability to predict TCRβ diversity across age, sex and Cytomegalovirus exposure using machine learning and linear modeling approaches.ResultsWe show that TCRβ diversity is almost entirely determined by two measurable repertoire features: repertoire size and the frequency of the 1,000 most abundant clones. Together, these features explain 96% of the variance in TCRβ diversity, capture its dependence on age and sex and define a robust relationship that persists under strong immune perturbations such as Cytomegalovirus infection. This relationship arises because the frequency of abundant clones, which represent less than one percent of TCRβ diversity, tracks a repertoire wide pattern of coordinated clonal expansion which we term intrinsic clonality.DiscussionWe propose that intrinsic clonality reflects a fundamental, previously unrecognized property of the immune system which challenges the view that TCR diversity declines primarily through passive erosion. Rather, TCR diversity emerges as a system level property mediated by repertoire size and intrinsic clonality, both of which are likely subject to homeostatic regulation. These findings offer a new conceptual framework for understanding TCR diversity within immune homeostasis which may guide therapies aimed at restoring immune function.